Whole farm simulation analysis of economic impacts of East Coast fever immunization strategies on mixed crop-livestock farms in Kenya - Nyangito, H.O.; Richardson, J.W.; Mukhebi, A.W.; Zimmel, P.; Namken, J.; Perry, Brian D. (Elsevier, 1996)
A whole farm simulation approach was used to assess the economic impacts of five alternative strategies for controlling East Coast fever (ECF), a cattle disease, on farms from two sites in Kenya. The strategies were also ranked using the stochastic dominance criterion to determine the most preferred one by risk-averse smallholder farmers. The strategies involve the current acaricide-based method and immunization control strategies using the infection and treatment method (ITM) in combination with different levels of acaricide use. The simulation results indicated that immunization strategies generated higher mean values for output variables; net present value, internal rate of return benefit-cost ratio, annual cash receipts, net cash farm income and net farm income than the currently used conventional method. In all cases, the immunization strategy in which acaricide use was reduced by 75 percent generated the highest values for the output variables. The stochastic dominance ranking criterion also indicated that this was the most preferred ITM strategy which also generated the highest confidence premium.